Family Purchase Decision: An Examination Of Teenagers’ Resources And Influence Strategies - Fikry@Aziz, Amily (2009)
This section begins with an overview of teenagers’ market. In the background of the study, based on previous studies, it is acknowledged that socioeconomic characteristics (i.e. resources) of teenagers exert an important influence on family purchase decisions